(untitled) - Beiser, Arthur (New York, 1987)
This text is written for a one-semester Modern Physics course and is designed for students who already have a grounding in basic physics and calculus. Relativity and quantum ideas are cosidered first to provide a framework for understanding the physics of atoms and nuclei. The theory of the atom is then developed, with emphasis on quantum-mechanical notions. This is followed by a discussion of the properties of aggregates of atoms, which includes a look at statistical mechanics. Finally, atomic nuclei and elementary particles are examined. New features include: second colour for emphasis; twice as many photographs; twice as many worked examples; and 25% more questions.
Keywords: Physics,Modern physics,Vật lý,Vật lý hiện đại